Effects of strain on the electronic structure and magnetic properties in SrMn0.5Fe0.5O3. (29th June 2016) - Mi, Chun-Wei; Chin, Yi-Ying; Hsiao, Yen-Fu; Fang, Hau-Wei; Luo, Chih-Wei; Wu, Kaung-Hsiung; Uen, Tzeng-Ming; Lin, Jiunn-Yuan; Lin, Hong-Ji; Juang, Jenh-Yih
Abstract: The electronic structure and magnetic properties of SrMn0.5 Fe0.5 O3 powder and films grown on (1 0 0)-SrTiO3 (STO) and (1 0 0)-LaAlO3 (LAO) substrates by pulsed laser deposition (PLD) were investigated by temperature dependent magnetization and soft x-ray absorption. The results exhibit characteristics of 3 d 5 Fe 3+, 3 d 5 L _ Fe 4 +, and 3 d 3 + 3 d 4 L _ Mn 4+ at room temperature in all samples. However, the features of 3 d 5 Fe 3+ and 3 d 3 Mn 4+ increased significantly for SMFO/LAO at 35 K, which also displayed substantial competition between antiferromagnetic and ferromagnetic order well-above the Néel temperature of SrFeO3 ( T N 134 K). We attributed this to being caused by charge disproportionation resulting from ligand-hole localization, which is more favorable to take place when the sample is under compressive strain.